Exome Sequencing by Targeted Enrichment. Issue 1 (1st April 2013) - Clark, Michael James; Chen, Rui; Snyder, Michael
Abstract: This unit describes methods for targeted enrichment of the exon‐coding portions of the genome using Agilent SureSelect Human All Exon 50 Mb and Roche Nimblegen SeqCap EZ Exome platforms. Each platform targets and enriches a large overlapping portion of the greater human exome. The protocols here describe the biochemical procedures used to enrich exomic DNA with each platform, including recommended modifications to the manufacturers' protocols. In addition, a brief description of the sequencing protocol and estimation of the needed amount of sequencing for each platform is included. Finally, a detailed analytical pipeline for processing the subsequent data is described. These protocols focus specifically on human exome sequencing platforms, but can be applied with some modification to other organisms and targeted enrichment approaches. Curr. Protoc. Mol. Biol . 102:7.12.1–7.12.21. © 2013 by John Wiley & Sons, Inc.